Types and determinants of migrants' settlement intention in China's new phase of urbanization: A multi-dimensional perspective. (May 2022) - Lin, Liyue; Zhu, Yu
Abstract: Using data from China Migrant Dynamic Survey, this paper provides an updated and comprehensive study on migrants' settlement intention and its determinants, based on a new way of conceptualizing and measuring such intention and its permanency and stability. The results suggest that although the majority of migrants have the intention to settle down in the destination cities on a permanent or long-term temporary basis, migrants with permanent settlement intention are still a minority, and there is a significant variation of migrants' settlement intention in terms of its permanency and stability among migrants, cities of different sizes, and geographical regions. The modelling results reveal that being married, higher levels of educational attainment, occupational status and income, family migration, and housing availability and stability of residence in the host city, boost migrants' long-term and permanent settlement intention. Moreover, migrants' urban origin and hukou status, higher occupational status, younger age, and the larger size, more economic prosperity and well-developed public services of their destination cities, significantly promote the permanent settlement intention. These results will facilitate relevant policy making to further advance China's urbanization, and contribute to better theoretical understanding of urban and mobility transitions in developing countries. Highlights: The majority of migrants in China have the intention to settle down in the destination cities on a permanent or long-term basis. However, migrants with permanent settlement intention are still a minority. The permanency and stability of migrant settlement intention vary significantly among migrants, cities of different sizes, and various regions. Urban origin and hukou status, high-skilled occupations and younger age promote the permanency and stability of migrant settlement intention. The larger city size, more economic prosperity and better public services promote the permanency and stability of migrant settlement intention.